(untitled) (African Journal of Law and Politics, 2023)
The appointment of public officials in Cameroon is a form of exercise of discretionary power framed by legality. This exercise, in fact, is subject of on the one hand to a certain number of rules intended to combat favoritism and nepotism in order to ensure equal access for citizens to the public service and, on the other hand, very strict jurisdictional control intended to ensure the observance by the appointing authority of the established regulations. Moreover, the legal framework for the freedom of choice of public officials by the political power has tended, in recent year, to be strengthened a little. In the meantime, public officials are, thanks to very strict regulation and jurisdictional control of the power of appointment, more and more effectively protected against administrative favoritism and arbitrariness. Of course, all is not yet for the best. The legal framework for the appointment still contains shortcomings, that is to say insufficiencies or even contradictions. Many questions remain unanswered. But the fact remains that the progress made in the regulation of the power of appointment is not negligible.